Effect of an injury prevention program on the lower limb stability in young volleyball players - Albaladejo-Saura, M.; Vaquero-Cristóbal, R.; Marcos-Pardo, P. J.; Esparza-Ros, F. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Volleyball players have a high risk of injury in the lower limbs as a consequence of the specific characteristics of the sport, such as repetitive jumps and falls. The objective of the present study was to evaluate the effects of a multidisciplinary injury prevention program on lower limb stability in young volleyball players. METHODS: The experimental design was a non-randomized controlled trial. All the measurements were performed in a standardized room in a sports center. Twenty-six young male volleyball players (mean age: 15.39±1.16 years), divided into experimental (N.=15) and control groups (N.=11) participated in this study. The experimental group performed an 8-week prevention program including lower limb strength and plyometric training, and joint and core stability. The Y-Balance and force platform landing tests were carried out as the pre- and post-tests. RESULTS: The main outcome measures were the injuries history, distance and difference reached in anterior, post-lateral and post-medial axis of the Y-Balance test, and the force produced on the z, x, and y axis after landing. Differences were found between groups and measurements in all the variables of the Y-Balance test, except in the frontal axis for the dominant leg and for the differences between legs (P=0.039-0.001); and in the ground reaction forces (z axis) (P=0.040), the x axis (P=0.014) and the dynamic postural stability index (P=0.025) of the lateral jump with the non-dominant leg. CONCLUSIONS: An 8-week prevention program seems to improve the lower limb stability in young volleyball players.